The psychometric characteristics of an assessment instrument for perceived harmfulness in adolescents with musculoskeletal pain (PHODA‐youth). (22nd September 2014) - Verbunt, J.A.; Nijhuis, A.; Vikström, M.; Stevens, A.; Haga, N.; de Jong, J.; Goossens, M.
Abstract Background Cognitive–behavioural models of chronic pain predict that dysfunctional assumptions about harmfulness of activities may maintain pain‐related fear and disability. To assess perceived harmfulness in adolescents, the Photograph Series of Daily Activities for youth (PHODA‐youth) was developed. Information concerning its methodological quality is currently lacking. Objective To investigate psychometric characteristics (factor structure, test–retest reliability, construct validity) and feasibility of the PHODA‐youth in adolescents with chronic musculoskeletal pain. Study design Test–retest design. Study population Adolescents aged 13–21 years with chronic nonspecific musculoskeletal pain. Methods Participants filled in an electronic version of the PHODA‐youth including 89 items twice with a 4‐week interval. The instrument's factor structure was determined by a factor analysis. Construct validity was studied with criterion variables: catastrophizing (Pain Catastrophizing Scale for Children), pain intensity (visual analogue scale), depression (Children's Depression Inventory) and pain‐related disability (Functional Disability Inventory) using regression analysis. Test–retest reliability was evaluated based on the Pearson correlation coefficient. Feasibility was studied with self‐constructed questions. Results Seventy‐one adolescents participated. Results show a three‐factor structure for the PHODA‐youth including 51 items with subscales labelled as: 'activities of daily life', 'intensive physical activities' and 'social activities'. Total and subscale scores showed a high internal consistency. Its test–retest reliability was good (r = 0.94) and its construct validity is supported by the finding that both catastrophizing (β = 0.25; p = 0.02) and disability (β = 0.71; p < 0.001) were uniquely related to the PHODA‐youth. In addition, feasibility appeared adequate. Conclusion The findings support the PHODA‐youth as a valid and reliable measure of the perceived harmfulness of activities in adolescents with musculoskeletal pain.